Wings of Their Dreams : Purdue in Flight, Second Edition - Norberg, John (Book collections on Project MUSE., 2019)
"Throughout 100-plus years of flight, Purdue University has propelled unique contributions from pioneer educators, aviators, and engineers who flew balloons into the stratosphere, barnstormed the countryside, helped break the sound barrier, and left footprints in lunar soil. Wings of Their Dreams follows the flight plans and footsteps of aviation's pioneers and trailblazers across the twentieth century, a path from Kitty Hawk to the Sea of Tranquility and beyond. The book reminds readers that the first and last men to land on the moon first trekked across the West Lafayette, Indiana, campus on their journeys into the heavens and history. This is the story of an aeronautic odyssey of imagination, science, engineering, technology, adventure, courage, danger, and promise. It is the story of the human spirit taking flight, entwined with Purdue's legacy in aviation's history."--